Activation of iNKT Cells Facilitates Liver Repair After Hepatic Ischemia Reperfusion Injury Through Acceleration of Macrophage Polarization - Goto, Takuya; Ito, Yoshiya; Satoh, Masashi; Nakamoto, Shuji; Nishizawa, Nobuyuki; Hosono, Kanako; Naitoh, Takeshi; Eshima, Koji; Iwabuchi, Kazuya; Hiki, Naoki; Amano, Hideki (Frontiers in Immunology, 2021)
Macrophage polarization is critical for liver tissue repair following acute liver injury. However, the underlying mechanisms of macrophage phenotype switching are not well defined. Invariant natural killer T (iNKT) cells orchestrate tissue inflammation and tissue repair by regulating cytokine production. Herein, we examined whether iNKT cells played an important role in liver repair after hepatic ischemia-reperfusion (I/R) injury by affecting macrophage polarization. To this end, we subjected male C57BL/6 mice to hepatic I/R injury, and mice received an intraperitoneal (ip) injection of α-galactosylceramide (α-GalCer) or vehicle. Compared with that of the vehicle, α-GalCer administration resulted in the promotion of liver repair accompanied by acceleration of macrophage differentiation and by increases in the numbers of Ly6Chigh pro-inflammatory macrophages and Ly6Clow reparative macrophages. iNKT cells activated with α-GalCer produced interleukin (IL)-4 and interferon (IFN)-γ. Treatment with anti-IL-4 antibodies delayed liver repair, which was associated with an increased number of Ly6Chigh macrophages and a decreased number of Ly6Clow macrophages. Treatment with anti-IFN-γ antibodies promoted liver repair, associated with reduced the number of Ly6Chigh macrophages, but did not change the number of Ly6Clow macrophages. Bone marrow-derived macrophages up-regulated the expression of genes related to both a pro-inflammatory and a reparative phenotype when co-cultured with activated iNKT cells. Anti-IL-4 antibodies increased the levels of pro-inflammatory macrophage-related genes and decreased those of reparative macrophage-related genes in cultured macrophages, while anti-IFN-γ antibodies reversed the polarization of macrophages. Cd1d-deficient mice showed delayed liver repair and suppressed macrophage switching, compared with that in wild-type mice. These results suggest that the activation of iNKT cells by α-GalCer facilitated liver repair after hepatic I/R injury by both IL-4-and IFN-γ-mediated acceleration of macrophage polarization. Therefore, the activation of iNKT cells may represent a therapeutic tool for liver repair after hepatic I/R injury.